Thermoelectric generators from SiO2/SiO2 + Ge nanolayer thin films modified by MeV Si ions. (January 2015) - Budak, S.; Gulduren, E.; Allen, B.; Cole, J.; Lassiter, J.; Colon, T.; Muntele, C.; Alim, M.A.; Bhattacharjee, S.; Johnson, R.B.
Abstract: We prepared thermoelectric generator devices from 100 alternating layers of SiO2 /SiO2 + Ge superlattice thin films using Magnetron DC/RF Sputtering. Rutherford Backscattering Spectrometry (RBS) and RUMP simulation software package were used to determine the proportions of Si and Ge in the grown multilayer films and the thickness of the grown multi-layer films. 5 MeV Si ion bombardments were performed using the AAMU-Pelletron ion beam accelerator, to form quantum clusters in the multi-layer superlattice thin films, in order to tailor the thermoelectrical and optical properties. We characterized the fabricated thermoelectric devices using cross-plane Seebeck coefficient, van der Pauw resistivity, mobility, density (carrier concentration), Hall Effect coefficient, Raman, Fluorescence, Photoluminescence, Atomic Force Microscopy (AFM) and Impedance analyzing measurements. Some suitable high energy ion fluences and thermal annealings caused some remarkable thermoelectrical and optical changes in the fabricated multilayer thin film systems.